Adiabatic tracking for photo- and magneto-association of Bose-Einstein condensates with Kerr nonlinearities; The European Physical Journal D; Vol. 70, iss. 12 - Gevorgyan M. Mariam; Guerin S. S.; Leroy C. Claude; Ishkhanyan A. Artur; Hans-Rudolf J. Jauslin (2016, 2016)
Title screen